A Pragmatic Analysis of Dialogue Between Two Characters in the Old Man and the Sea Based on the Cooperative Principle - Rasheed, Mohammed Hameed (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study conducts a pragmatic analysis of the dialogue between characters in Ernest Hemingway's "The Old Man and the Sea," utilizing Grice's Cooperative Principle as a theoretical framework. By examining the interactions between Santiago and Manolin, the research highlights how conversational maxims: Quality, Quantity, Relation, and Manner shape their communication. The analysis reveals that while both characters generally adhere to these principles, occasional deviations occur, reflecting their emotional connections and the complexities of their relationship. This investigation not only enhances understanding of the characters' dynamics but also underscores the broader implications of pragmatic theory in literary dialogue. Ultimately, the findings demonstrate that effective communication transcends mere information exchange, emphasizing the importance of fostering relationships and emotional understanding in human interactions.